Barriers and Facilitators Related to Undertaking Physical Activities in Colorectal Cancer Patients: A Scoping Review - Yan, Hu; Shuying, Chang; Yuege, Li; Han, Kong (Oncology Reviews, 2024)
Background: Colorectal cancer (CRC) and its treatments cause significant acute, chronic, or latent adverse effects, leading to decreased physical function and quality of life. Robust evidence supports the positive effects of physical activity (PA) on various health outcomes in CRC patients. However, there is limited understanding regarding the factors that influence PA engagement, including facilitators, preferences, and barriers in this population. Purpose: This scoping review aims to document the breadth and depth of literature concerning the various aspects of PA participation among patients with CRC. We conducted a scoping review of PA among CRC patients. Methods: We searched several databases, including PubMed, Web of Science, Embase, and Cochrane, from their inception to 25 July 2023. Multiple reviewers were involved in all screening and data abstractions. The search yielded 834 individual citations after removing duplicates. After screening the titles and abstracts, 20 articles underwent full-text review, and 11 were included. Results: Our research findings indicate that among CRC patients, the most prevalent facilitators/preferences for PA are understanding its importance and perceiving its benefits, whereas treatment-related effects and lack of time are the most common barriers. Conclusion: CRC patients have unique facilitators and barriers concerning PA. Further research and clinical interventions are required to support and encourage this population to participate in and maintain regular PA.